Economic evaluation of alternative hepatitis C treatment options: a post hoc analysis of the VIETNARMS trial - Turner,H; Ahmed,S; Nguyen,HA; Hung,LM; Nuil,JV; Trong,TD; Dung,NT; Thwaites,GE; Walker,AS; Vinh,Chau NV; Cooke,GS; Hallett,TB (EClinicalMedicine, 2026)
BackgroundHepatitis C remains a leading cause of liver disease worldwide, and access to Direct-Acting Antiviral (DAA) treatment remains limited in many settings. Alternative treatment strategies that require fewer tablets and clinical visits could help improve equitable access, and new approaches have recently been found to be non-inferior in producing sustained viral suppression. MethodsWe did a cost-minimization analysis of alternative treatment options for non-cirrhotic patients evaluated in the VIETNARMS trial (ISRCTN61522291), conducted between 19/06/2020 and 10/05/2023 in Vietnam. These were: (i) ‘response guided’ (which adjusts treatment duration based on 1-week viral load); (ii) ‘induction maintenance’ (which reduces the dosing frequency in later weeks of treatment); and (iii) ‘Peg-IFN+DAA’ (4 weeks of DAAs combined with four weekly doses of PEGylated interferon (Peg-IFN). The primary outcome was the cost per cure. A disaggregated societal perspective was adopted, including stratification for the healthcare provider and patient costs. FindingsThe three alternative treatment strategies were projected to have lower costs per cure than standard 12-week DAA treatment in the base-case scenario: US$202 (15%) less for ‘response guided’, US$234 (18%) less for ‘induction maintenance’, and US$163 (12%) less for ‘Peg-IFN+DAA’. However, the potential for cost savings, and which strategy had the lowest cost per cure, depended on the assumed cost of DAA drugs: the strategy with the lowest cost per cure was generally ‘induction maintenance’ when DAA drug costs for a standard treatment course were under US$1,000, but Peg-IFN+DAA when DAA costs exceeded US$1,500. In some scenarios, lower costs per cure were achieved through reduced health system expenditures, despite increased costs to patients.InterpretationAlternative strategies for Hepatitis C treatment could reduce costs for providers an